Extreme tooth enlargement in a new Late Cretaceous rhabdodontid dinosaur from Southern France. Issue 1 (December 2017) - Godefroit, Pascal; Garcia, Géraldine; Gomez, Bernard; Stein, Koen; Cincotta, Aude; Lefèvre, Ulysse; Valentin, Xavier
Abstract Rhabdodontidae is a successful clade of ornithopod dinosaurs, characteristic of Late Cretaceous continental faunas in Europe. A new rhabdodontid from the late Campanian, of southern France, Matheronodon provincialis gen. et sp. nov., is characterized by the extreme enlargement of both its maxillary and dentary teeth, correlated to a drastic reduction in the number of maxillary teeth (4 per generation in MMS/VBN-02-102). The interalveolar septa on the maxilla are alternately present or resorbed ventrally so as to be able to lodge such enlarged teeth. The rhabdodontid dentition and masticatory apparatus were adapted for producing a strict and powerful shearing action, resembling a pair of scissors. With their relatively simple dentition, contrasting with the sophisticated dental batteries in contemporary hadrosaurids, Matheronodon and other rhabdodontids are tentatively interpreted as specialized consumers of tough plant parts rich in sclerenchyma fibers, such asSabalites andPandanites .